The Endurance Profile’s Basketball Player Santa Maria Kediri Junior High School - Shandy Pieter Pelamonia; Achmad Nuryadi; Eka Kurnia Darisman (CV. SAMODRA INSAN PENA, 2025)
Endurance is a key physical component influencing performance in basketball, particularly in school-based competitive contexts. This study aimed to examine the aerobic and anaerobic endurance profiles of junior high school basketball players as a basis for training program development. A descriptive survey design was employed involving ten male basketball players (aged 14–16 years) from Santa Maria Junior High School, Kediri. Aerobic endurance was assessed using the 20-m multistage fitness test to estimate VO₂max, while anaerobic endurance was measured using the Running-Based Anaerobic Sprint Test (RAST). Data were analyzed using descriptive statistics and categorized based on normative standards. The results showed that aerobic endurance (VO₂max) was predominantly in the fair category, with 40% of athletes classified as poor and only 20% classified as very good. In contrast, anaerobic endurance was generally high, with 80% of athletes classified as very good. These findings indicate an imbalance between aerobic and anaerobic endurance capacities. The study highlights the need for greater emphasis on aerobic conditioning within school basketball training programs to support recovery and sustain performance during competition.